The Politeness Strategy of the Main Character of the Short Story “Abu Sir wa Abu Qir”: Brown Levinson - Bariqo Miski Firdausi; Dien Nur Chotimah (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study aims to analyze the politeness strategies of the main character in the short story “Abu Sir wa Abu Qir” by Kamil Kaylani using Brown and Levinson's theoretical framework. This research focuses on the politeness strategies used by the main characters in the short story Abu Sir wa Abu Qir to maintain their social face in various interaction situations. This research uses descriptive qualitative approach with reading and note-taking method. The data sources used are dialog excerpts in the short story Abu Sir wa Abu Qir. And the data analysis is done by identifying and classifying the speech of the two main characters based on the types of positive and negative politeness strategies used. The results of this study show the existence of positive politeness strategies in the form of offering or promising something, giving attention, giving praise to the interlocutor. Meanwhile, negative politeness strategies in this short story are in the form of indirect expressions & question expressions. In this short story, politeness strategies reflect the values and cultural norms of society, showing that politeness not only functions as manners, to maintain social harmony